Defective mitochondrial protease LonP1 can cause classical mitochondrial disease. (6th March 2018) - Peter, Bradley; Waddington, Christie L; Oláhová, Monika; Sommerville, Ewen W; Hopton, Sila; Pyle, Angela; Champion, Michael; Ohlson, Monica; Siibak, Triinu; Chrzanowska-Lightowlers, Zofia M A; Taylor, Robert W; Falkenberg, Maria; et al.
Abstract: LonP1 is a mitochondrial matrix protease whose selective substrate specificity is essential for maintaining mitochondrial homeostasis. Recessively inherited, pathogenic defects in LonP1 have been previously reported to underlie cerebral, ocular, dental, auricular and skeletal anomalies (CODAS) syndrome, a complex multisystemic and developmental disorder. Intriguingly, although classical mitochondrial disease presentations are well-known to exhibit marked clinical heterogeneity, the skeletal and dental features associated with CODAS syndrome are pathognomonic. We have applied whole exome sequencing to a patient with congenital lactic acidosis, muscle weakness, profound deficiencies in mitochondrial oxidative phosphorylation associated with loss of mtDNA copy number and MRI abnormalities consistent with Leigh syndrome, identifying biallelic variants in the LONP1 (NM_004793.3) gene; c.1693T > C predicting p.(Tyr565His) and c.2197G > A predicting p.(Glu733Lys); no evidence of the classical skeletal or dental defects observed in CODAS syndrome patients were noted in our patient. In vitro experiments confirmed the p.(Tyr565His) LonP1 mutant alone could not bind or degrade a substrate, consistent with the predicted function of Tyr565, whilst a second missense [p.(Glu733Lys)] variant had minimal effect. Mixtures of p.(Tyr565His) mutant and wild-type LonP1 retained partial protease activity but this was severely depleted when the p.(Tyr565His) mutant was mixed with the p.(Glu733Lys) mutant, data consistent with the compound heterozygosity detected in our patient. In summary, we conclude that pathogenic LONP1 variants can lead to a classical mitochondrial disease presentations associated with severe biochemical defects in oxidative phosphorylation in clinically relevant tissues.